The effect of neonatal asphyxia on renal function - Elly Nova Lubis; Srie Yanda; Khainir Akbar; Guslihan Dasa Tjipta; Dachrul Aldy (Indonesian Pediatric Society, 2001)
Neonatal asphyxia can cause renal perfusion and dilution disorders and also glomerular filtration abnormality. The purpose of this study was to find renal dysfunction, which caused by neonatal asphyxia. The study was performed by cross sectional for newborn babies with asphyxia based on Apgar score in the first minute. Newborn babies without asphyxia were as control. In both group, the first micturition times were recorded, total urine output in 24 hours were counted, the mean of blood urea and creatinine serum level value examined and also glomerular filtration rate. Statistical analysis has been performed by using Fisher Exact test, Student t test and Wilcoxon Rank Sum test. All of babies in the asphyxiated and non asphyxiated group had the first micturition in 24 hours after delivery. Significant difference of oliguria incidence was found in the asphyxiated group compared to the control group (p<0,05). The mean of blood urea and creatinine serum level was significantly higher in asphyxiated (p<0,05). The mean of glomerular filtration rate in the asphyxiated group was not significantly different to the control group (p>0,05). According to the degree of asphyxia we found significantly different of renal dysfunction (p<0,05). It was concluded that the asphyxia could cause the occurrence of renal dysfunction.Â